The dual capture of AsV and AsIII by UiO-66 and analogues. Issue 10 (7th July 2016) - Audu, Cornelius O.; Nguyen, Huong Giang T.; Chang, Chih-Yi; Katz, Michael J.; Mao, Lily; Farha, Omar K.; Hupp, Joseph T.; Nguyen, SonBinh T.
Abstract : UiO-66 and analogues were successfully tailored to chemoselectively capture As V oxyanions at the hydroxylated node and neutral As III species with the thiolated organic linkers. More efficient and faster uptake of As V can be achieved with increasing defect densities, increasing pore aperture sizes, and decreasing particle sizes. Abstract : UiO-66 and analogues were successfully tailored to chemoselectively capture As V oxyanions at the hydroxylated node and neutral As III species with the thiolated organic linkers. More efficient and faster uptake can be achieved with increasing defect densities, increasing pore aperture sizes, and decreasing particle sizes.